Biodiesel as alternative additive fuel for diesel engines: An experimental and theoretical investigation on emissions and performance characteristics - Kaya, Cenk; Kokkulunk, Gorkem (TAYLOR & FRANCIS INC, 2023)
The use of fossil-based fuels in internal combustion engines has become a major challenge and faces with serious transformation regarding emissions. Herein, alternative fuel usage becomes prominent, thanks to a great reduction of these emissions. In this study, using 20% (B20), 50% (B50), and 100% (B100) of waste frying oil biodiesel (WFOB)-diesel blends has been experimentally and theoretically investigated on emission and performance parameters at full load conditions of 1,500-3,000 rpm ranges in the diesel engine. According to the experimental results, it has been shown that torque has not changed significantly, but brake specific fuel consumption enhanced up to 12.98% owing to the lower heating value of biodiesel. In terms of emissions, biodiesel fuels reveal different results. Whereas HC, CO2, and NO(x)slightly increase with B100, all emissions almost reduce with B20, including NO(x)and smoke opacity. Maximum reductions of B20 are obtained as 4.51% in CO2, 29.27% in CO, 39.06% in HC, 6.52% in NOx, and 25% in smoke opacity emissions. In compliance with theoretical results, usage of biodiesel reduces exergy destruction rate as up to 7.03% and increases exergetic efficiency as up to 5.86% compared to neat diesel except 2,700-3,000 rpm. Consequently, the small addition of waste frying oil biodiesel as 20% is an optimum solution under favor of minimum increase of specific fuel consumption and reduction in all emissions.
Keywords: Waste frying oil biodiesel; waste cooking oil biodiesel; diesel engine; exergy; emissions; WASTE COOKING OIL; INJECTION PRESSURE; EXHAUST EMISSIONS; METHYL-ESTERS; NOX EMISSIONS; COMBUSTION; BLENDS; JATROPHA; IMPACT; SPEED; Energy & Fuels; Engineering; Environmental Sciences & Ecology